2013
DOI: 10.4103/0019-5545.105554
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care: Indian perspective

Abstract: According to Hinduism, the main religion of India, the end-of-life (EOL) deals with good and bad death. The WHO definition of palliative care stresses on improving not only the quality of life of patients facing incurable diseases but also their families by providing relief from the pain and suffering that includes the psychosocial and spiritual needs as well. The Indian Society of Palliative Care has been doing a commendable work and appreciable efforts are being done by the Kerala model of delivering the EOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…However, it has been identified that less than 2% of Indians in need of palliative care have access to palliative care services (Sharma et al. ). The Global Atlas of Palliative Care reported that palliative and end‐of‐life care provision in India is categorised as grade 3A – a generalized provision of care (Worldwide Palliative Care Alliance and World Health Organisation ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been identified that less than 2% of Indians in need of palliative care have access to palliative care services (Sharma et al. ). The Global Atlas of Palliative Care reported that palliative and end‐of‐life care provision in India is categorised as grade 3A – a generalized provision of care (Worldwide Palliative Care Alliance and World Health Organisation ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to many other countries (Gao et al 2013), hospital services are greatly utilized (76%) during the last days of life among Indians (Directorate General of Health Services, 2012). However, it has been identified that less than 2% of Indians in need of palliative care have access to palliative care services (Sharma et al 2013). The Global Atlas of Palliative Care reported that palliative and end-oflife care provision in India is categorised as grade 3Aa generalized provision of care (Worldwide Palliative Care Alliance and World Health Organisation 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hindus may underreport pain believing pain to be a sign of a bad death. 29 Hindu patients may view suffering as a result of karma, the sum of a person's actions in one's current and previous lives that influence one's fate, and thus be disinclined to seek treatment for pain, 14 however, a belief in karma need not necessarily interfere with treatment of pain and suffering at the end of life. 18 Experts recommend that, as with all other aspects of end-of-life care, decisions regarding pain management should be based on a thorough biopsychosocial assessment and made by health care providers in partnership with patients and families, based on their unique needs and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of awareness among professionals, administrators, educators and the public along with narcotic regulation also add to the list of barriers [9] . At the same time they also come with the unique strength associated with an intact family structure and values and spiritual lifestyle [13][14]. Because of the uniqueness of the ethical dilemmas and issues of the region it is difficult to explain them with the western model of palliative care ethics.…”
mentioning
confidence: 99%
“…Firstly the decision making is not done by the patient alone. This is a task which involves the family members as well as the physician [14] . Secondly the physician is considered next to God [15].…”
mentioning
confidence: 99%